The Relationship between Organic Matter and Soil Reflectance at Ramadi Iraq - Eilaf Abbas; Omar Al-Jarrah (Iraqi Geological Journal, 2023)
Soil characteristics change with certain stimuli, which change their reflectivity and therefore lose their characteristic properties. This research focuses on measuring the effect of organic matter on soil reflectivity, especially the lack of any standard soil reflectivity samples in the research area, and will be the first step in designing these diagrams. Pear leaf was selected, the leaves were taken, then buried at depths 40 cm and 100 cm. and their reflectivity and surrounding soil were measured for 6-months period. The results showed that the rate of reflectivity decreased by 26% during this periods at a wavelength of 900nm with an increase in organic matter on depth 40cm, reflectivity decreased by 13% during this periods in wavelength of 900nm with increasing in the organic carbon in the depth of 100cm ,and no clear effect of humidity on organic matter changes was observed. These results should be used in any future study of the area of research, and the difference in reflectivity should be calculated to prevent miscalculations in the future.